The Effect of The Power of Two Learning Strategies on Natural Science Material on the Thinking Ability of PGMI Students - Dinda Patliana Sukma (Yayasan Zia Salsabila, 2023)
Through the cooperative learning model, students will work together in their groups, then discuss some information, and disclose it to other groups. One type of cooperative learning, namely The Power Of Two Type. (The strength of both types) is learning in small groups by cultivating maximum cooperation through learning activities by friends themselves with two members in it to achieve basic competence. In this qualitative study, the literature review must be used consistently with methodological assumptions. This means that it must be used inductively so as to be able to answer the questions posed by the researcher.